Comparison of farming income for leek and Batu 55 tangerines in Batu City - Utami, Sri; Gunawan, Cakti Indra; Santosa, Budi (AGROMIX, 2024)
Introduction: Batu City is a horticultural center in East Java. One of the vegetable horticultural commodities cultivated by Batu City farmers is leeks. With the development of tangerine commodities in East Java established by the Directorate General of Horticulture in 2009 through the Program of "Keproknisasi Nasional", many farmers have switched their farming from leeks to stone tangerines 55. The research aim was to determine the difference in income of farming leek and tangerines farming in Batu 55; The sampling technique in this study is a purposive sampling technique, namely 50 farmer respondents who changed from farming leeks to Batu 55 tangerine farming in Batu City. Methods: analysis of income differences using the Paired Samples T-Test. Results: There is a real difference between leek farming income and Batu 55 tangerine farming. The average income of farming leeks is IDR 90.248.250,-/Ha while the average income of Batu 55 tangerine farming is IDR 315,037,000,-/Ha. Conclusion: The income from Batu 55 tangerine farming is greater than that of leek farming and there is a real difference between the income of leek farming and Batu 55 tangerine farming.